2019
DOI: 10.3389/fimmu.2019.00758
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Biomarkers to Diagnose Acute Allograft Rejection After Liver Transplantation: Systematic Review and Meta-Analysis of Diagnostic Accuracy Studies

Abstract: Objective: A systematic review and meta-analysis of diagnostic biomarkers for noninvasive diagnosis of acute allograft rejection following liver transplantation. Background: Noninvasive blood and urine markers have been widely explored in recent decades for diagnosing acute rejection after liver transplantation. However, none have been translated into routine clinical use so far due to uncertain diagnostic accuracy, and liver biopsy remains the gold standard. Met… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 47 publications
0
30
0
Order By: Relevance
“…Recent studies continue these correlations, proposing eosinophil blood counts as a biomarker for acute liver rejection . Yet a recent meta‐analysis of >800 patients and >1000 sample points indicated that blood eosinophil counts are highly heterogeneous and have only a 50% sensitivity for predicting acute liver rejection . Despite the fact that limited mechanistic evidence was provided by any of these studies, the destructive role of eosinophils was inferred from their increase at the time of rejection.…”
Section: Eosinophils In Solid Organ Transplantationmentioning
confidence: 99%
“…Recent studies continue these correlations, proposing eosinophil blood counts as a biomarker for acute liver rejection . Yet a recent meta‐analysis of >800 patients and >1000 sample points indicated that blood eosinophil counts are highly heterogeneous and have only a 50% sensitivity for predicting acute liver rejection . Despite the fact that limited mechanistic evidence was provided by any of these studies, the destructive role of eosinophils was inferred from their increase at the time of rejection.…”
Section: Eosinophils In Solid Organ Transplantationmentioning
confidence: 99%
“…The role of eosinophils in rejection has often been debated [33] and there is a discussion on whether eosinophils may be the target of rejection therapy [34]. An increase in the rejection of eosinophils has also been reported in the transplanted liver [35]. In the small intestine, the presence of the mucosal immune system may further complicate the graft's immunological environment.…”
Section: Nkt Cells and Cytokinesmentioning
confidence: 99%
“…Although noninvasive tests are currently under development, liver biopsy remains the gold standard for diagnosis of rejection. 5 Liver biopsies are able to assist in diagnosing other causes of hepatic diseases, including drug-induced liver injury, immune-mediated processes, hepatotropic viruses, and chronic biliary obstruction, in addition to providing details about the amount of fibrosis. 6…”
Section: Clinical Presentationmentioning
confidence: 99%